Heat transfer by low-frequency phonons and "diffusive" modes in cryocrystal solutions: the Kr–Xe system: Low-Temperature Thermodynamics and Structure - Konstantinov, V.A.; Orel, E.S.; Revyakin, V.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The temperature and volume dependences of the thermal conductivity of the Kr1–x Xex solid solution are analyzed in a model in which heat is transferred by low-frequency phonons; above the phonon mobility edge this is done by "diffusive" modes migrating randomly from site to site. Thephonon mobility edge w0 is determined from the condition that the phonon mean free path limitedby umklapp processes and scattering on point defects cannot be smaller than one-half the phonon wavelength. The Bridgman coefficientg g = - (¶ ln / L ¶ ln V)T is the weighted mean over these modes, whose volume dependences differ strongly. It is shown that the amount of heat transferred by the "diffusive" modes above 100 K is quite large even in pure Kr and it increases with rising temperature and impurity concentration.